HUBUNGAN KOMPLIKASI DIABETES MELLITUS DENGAN KUALITAS HIDUP PASIEN DIABETES MELLITUS - Utami Maulina Hutabarat; Yesi Hasneli; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Diabetes Mellitus (DM) is called silent killer that was characterized by an increasing in blood glucose levels and failure of insulin secretion or insulin in inadequate metabolism causing symptoms of hyperglycemia. The purpose of this study was to determine the relationship between DM complications and the quality of life of DM patients. This research method uses a descriptive correlation research design with a cross sectional approach. This research was carried out at Puskesmas Harapan Raya Pekanbaru with 83 respondents with DM complications using purposive sampling technique, based on inclusion criteria. The results showed that from 83 respondents, there were 41 diseases (77.4%) and one high quality of life, while 26 respondents (86.7%) had more than one complication and low quality of life. Data processing used in this study was Chi-Square test. The results showed p value <0.05 its means that there was a relationship between DM complications and quality of life of DM patients with p = 0,000. Keywords: Complications, Diabetes Mellitus (DM), quality of life